STRATEGI GURU DALAM MENINGKATKAN PARTISIPASI SISWA SLOW LEARNER DI SDN 17 LIMBOTO - Misilu, Fikriyan; Munirah, Munirah; Mohamad, Sabrina Nadjib (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2026)
AbstractThis study aims to provide an in-depth analysis of the various tactics employed by teachers at SDN 17 Limboto. The goalss is to understand how they identify the characteristics of students with slower learning abilities (Slow Learners). This study uses qualitative research with a descriptive approach. Data were collected through observation, interviews, and documentation. Participants or subjects of this study were homeroom teachers of grades II and IV. The results show that the strategies applied by teachers include individual attention to Slow Learner students, simplification of teaching materials, the use of various learning methods and media, along with the provision of motivation and positive affirmations. However, the level of student participation has not reached the optimal point due to several obstacles, such as limited learning time allocation, variations in capabilities between students, and the lack of supporting facilities and infrastructure. Therefore, it can be concluded that accurate, consistent, and continuous teaching tactics from teachers have a significant impact on optimizing the engagement of Slow Learner students. This study recommends that initiatives to increase the participation of Slow Learner students need to be pursued sustainably by involving various elements, so that learning targets can be realized more perfectly. Keywords: Teacher Strategy, Increasing, Student ParticipationAbstrakPenelitian atau riset ini bertujuan pada penelaahan mendalam tentang berbagai taktik yang diterapkan oleh pengajar di SDN 17 Limboto. Tujuannya adalah memahami bagaimana mereka mengidentifikasi ciri-ciri peserta didik dengan kemampuan belajar lebih lambat Slow Learner. Penelitian ini menggunakan penelitian kualitatif dengan pendekatan Deskriptif. Data dikumpulkan melalui observasi,wawancara dan dokumentasi. Partisipan atau subjek penelitian ini adalah guru wali kelas II dan IV. Hasil penelitian memperlihatkan bahwa strategi yang diaplikasikan oleh guru mencakup atensi individual pada siswa Slow Learner, simplifikasi materi ajar, pemanfaatan metode serta media pembelajaran yang beragam, berikut pemberian motivasi dan afirmasi positif. Walaupun demikian, level partisipasi siswa belum mencapai titik optimal akibat sejumlah kendala, seperti alokasi waktu belajar yang terbatas, variasi kapabilitas antar siswa, serta minimnya fasilitas dan infrastruktur penunjang. Oleh karena itu, dapat ditarik kesimpulan bahwa taktik pengajaran yang akurat, ajek, dan berkesinambungan dari guru memiliki dampak signifikan dalam mengoptimalkan keterlibatan siswa Slow Learner. Oenelitian ini merekomendasikan agar inisiatif untuk meningkatkan partisipasi siswa slow learner perlu diupayakan secara berkelanjutan dengan melibatkan berbagai elemen, sehingga target pembelajaran dapat direalisasikan secara lebih sempurna. Kata Kunci: Strategi Guru, Meningkatkan, Partisipasi Siswa